1989
DOI: 10.1128/jb.171.12.6740-6746.1989
|View full text |Cite
|
Sign up to set email alerts
|

Parathion hydrolase specified by the Flavobacterium opd gene: relationship between the gene and protein

Abstract: The sequence of a 1,693-base-pair plasmid DNA fragment from Flavobacterium sp. strain ATCC 27551 containing the parathion hydrolase gene (opd) was determined. Within this sequence, there is only one open reading frame large enough to encode the 35,000-dalton membrane-associated hydrolase protein purified from Flavobacterium extracts. Amino-terminal sequence analysis of the purified Flavobacterium hydrolase demonstrated that serine is the amino-terminal residue of the hydrolase protein. The amino-terminal serin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(145 citation statements)
references
References 22 publications
(14 reference statements)
3
141
1
Order By: Relevance
“…Recombinant expression of OPH usually results in low active enzyme yield due to low solubility of this protein in E. coli (Mulbry and Karns 1989a;Grimsley et al 1997). Though several approaches have been investigated for improved production of OPH in recombinant systems, including multi-gene fusions (Wu et al 2001), fusion with highly-soluble fusion partners (Cha et al 2000), display on cell surface (Richins et al 1997;Li et al 2004), and periplasmic secretion (Kang et al 2005), reaching high productivity of OPH using E. coli-based fermentation or in other recombinant systems (Takayama et al 2006) is still challenging, especially for further cost-efficient production of highly purified enzymes for electrochemical biosensor applications.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant expression of OPH usually results in low active enzyme yield due to low solubility of this protein in E. coli (Mulbry and Karns 1989a;Grimsley et al 1997). Though several approaches have been investigated for improved production of OPH in recombinant systems, including multi-gene fusions (Wu et al 2001), fusion with highly-soluble fusion partners (Cha et al 2000), display on cell surface (Richins et al 1997;Li et al 2004), and periplasmic secretion (Kang et al 2005), reaching high productivity of OPH using E. coli-based fermentation or in other recombinant systems (Takayama et al 2006) is still challenging, especially for further cost-efficient production of highly purified enzymes for electrochemical biosensor applications.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we attempted to identify organophosphorus hydrolase gene by PCR. Among OPhydrolyzing enzymes, the most studied so far is a product of opd gene, which was found in Sphingobium fuliginis [27,59], Brevundimonas diminuta GM [17,27], and in several representatives of genera Pseudomonas and Agrobacterium (in the latter case the gene is designnated opdA) [24][25][26]60]. Detection of the gene in the POXN01 strain was performed according to an established protocol that relies on analytical PCR with opdspecific primers [32].…”
Section: Resultsmentioning
confidence: 99%
“…ATCC 27551 [62], and from two unidentified strains, B-1 and SC [56]. In the former two organisms, it is a 35-kDa, membrane-associated enzyme, and in P. diminuta it appears to exist as a dimer [61].…”
Section: Phosphorothionate Insecticides -Parathion and Malathionmentioning
confidence: 99%
“…ATCC 27551 have both been shown to be encoded on large plasmids, pCMS1 (51 kb) and pPDL2 (39 kb (also called pSM55; 43 kb [64]), respectively [61,62]. The two opd (organophosphate degradation) genes have been cloned and sequenced [61,62,65], and proved to be 100% identical [64], although restriction mapping confirmed that the plasmids carrying them differed extensively [64]. Both of these enzymes are produced constitutively, and have usually been purified from nutrient broth cultures grown without addition of phosphotriesters as inducers.…”
Section: Phosphorothionate Insecticides -Parathion and Malathionmentioning
confidence: 99%